Asking Survey Questions About Criminal Justice Involvement. (May 2019) - Yan, Ting; Cantor, David
Criminal justice involvement is a multifaceted construct encompassing various forms of contact with the criminal justice system. It is a sensitive topic to ask about in surveys and also a sensitive topic for respondents to answer. This article provides guidance for writing survey questions on criminal justice involvement, starting with a review of potential causes for reporting error and nonresponse error associated with survey questions on criminal justice involvement. Questions about criminal justice involvement are subject to errors that are common to any survey (eg, misunderstanding questions, recall bias, telescoping). Reponses to these questions are also subject to underreporting because of social desirability concerns. We also address strategies to reduce error for questions pertaining to criminal justice involvement (eg, self-administered data collection, wording of forgiving questions, indirect methods). We then discuss common design decisions associated with writing survey questions on criminal justice involvement (eg, type and frequency of criminal justice involvement, reference period, ) and provide examples of questions from current surveys.